2017
DOI: 10.1103/physrevlett.119.185001
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Electron Bernstein Wave Heating in a Reversed Field Pinch

Abstract: The first observation of rf heating in a reversed field pinch (RFP) using the electron Bernstein wave (EBW) is demonstrated on the Madison Symmetric Torus. Propagation across and heating in a stochastic magnetic field is observed. Novel techniques are required to measure the suprathermal electron tail generated by EBW heating in the presence of intense Ohmic heating. rf-heated electrons directly probe the edge transport properties in the RFP; measured loss rates imply a large noncollisional radial diffusivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The slow X-mode will then reach the UHR and excite the EBW. Like the O-X-B mode-conversion, the X-B mode-conversion has been welldemonstrated experimentally [32,33,34]; unlike the O-X-B mode-conversion, however, the X-B mode-conversion is difficult to study analytically, and is typically studied computationally with particle-in-cell methods [35,36,37] or full-wave solvers [38,39]. This trend can probably be attributed in large part to the inherent non-locality of the X-B mode-conversion, which will be elucidated in the following section.…”
Section: Introductionmentioning
confidence: 94%
“…The slow X-mode will then reach the UHR and excite the EBW. Like the O-X-B mode-conversion, the X-B mode-conversion has been welldemonstrated experimentally [32,33,34]; unlike the O-X-B mode-conversion, however, the X-B mode-conversion is difficult to study analytically, and is typically studied computationally with particle-in-cell methods [35,36,37] or full-wave solvers [38,39]. This trend can probably be attributed in large part to the inherent non-locality of the X-B mode-conversion, which will be elucidated in the following section.…”
Section: Introductionmentioning
confidence: 94%
“…Recent studies [15] demonstrated RF heating in the RFP configuration using the EBW on Madison Symmetric Torus. A challenging heating environment exists in the RFP, where electromagnetic wave cutoffs occur within ~1cm of the edge and enclose the plasma volume due to an overdense plasma with no high field side.…”
Section: Ebw Heating Overviewmentioning
confidence: 99%
“…In the last few years, the study of electron Bernstein waves in plasma has been a particular field of interest due to its many applications in plasma heating [1], acceleration of charge particles [2], harmonic generation [3] and diagnostics [4]. The linear [5] and nonlinear [6] coupling of waves in plasmas is a promising nature for application in producing resonant heating of high β plasma and power excitation.…”
Section: Introductionmentioning
confidence: 99%